2007
DOI: 10.1007/s10815-007-9134-9
|View full text |Cite
|
Sign up to set email alerts
|

Is there a recommended maximum starting dose of FSH in IVF?

Abstract: This report reviews and discusses the existing evidence on recommended FSH doses in IVF cycles. A comprehensive search for relevant data was performed in the Cochrane Library, MEDLINE, EMBASE and NICE clinical guidelines database, and the reference lists of manuscripts. A good body of evidence exists looking at starting doses of FSH for first IVF attempts. Only one randomised controlled trial was identified looking at the efficacy of increasing doses during an IVF cycle. Some observational studies dealt with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
(28 reference statements)
1
14
0
3
Order By: Relevance
“…Our observations are consistent with those made in other studies, which suggest that the likelihood of pregnancy reaches a plateau after retrieval of approximately 15 oocytes, but the risk of OHSS increases significantly with ovarian responses above this threshold . Other observational studies have also demonstrated that increasing doses of gonadotropin are associated with reduced rates of pregnancy or live birth, and have inferred that high FSH doses may have a direct effect on oocytes or an indirect effect via a rise in follicular‐phase progesterone on endometrial receptivity …”
Section: Discussionsupporting
confidence: 92%
“…Our observations are consistent with those made in other studies, which suggest that the likelihood of pregnancy reaches a plateau after retrieval of approximately 15 oocytes, but the risk of OHSS increases significantly with ovarian responses above this threshold . Other observational studies have also demonstrated that increasing doses of gonadotropin are associated with reduced rates of pregnancy or live birth, and have inferred that high FSH doses may have a direct effect on oocytes or an indirect effect via a rise in follicular‐phase progesterone on endometrial receptivity …”
Section: Discussionsupporting
confidence: 92%
“…The data from the Trust trial analyzed in this study also successfully illustrate the regression to the mean effect in patients with an extreme response (i.e., low response or high response) (10). In the Trust study, 45.8% of low/high responders in cycle 1 went on to have a normal response in cycle 2 without changes in the stimulation protocol (Supplemental Table 8).…”
Section: Discussionmentioning
confidence: 71%
“…Статистические данные обсчета вторичных точек исследования: применение сравниваемых препаратов Примапур ® и Гонал-ф ® статистически не отличается по количеству проведенных переносов на 3-й и 5-й день развития эмбрионов. женщин с нормальным овариальным резервом, в циклах с антагонистами ГнРГ и стартовой дозой ФСГ, равной 150 МЕ [16][17][18][19][20][21][22].…”
Section: результаты и обсуждениеunclassified